Influence of reputation, religiosity and transparency on the belief of muzakki paying zakat at Baitul Mal Banda Aceh - Akhsanun Nadia; Nurma Sari (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2023)
Abstract Purpose – This research is to analyze the effect of reputation, religiosity, and transparency on muzakki's trust in paying zakat in Baitul Mal Banda Aceh Method – This study collected primary data by distributing questionnaires to 100 respondents using a random sampling technique. Technical data analysis was carried out using multiple regression tests with the SPPS analysis tool. Research result - The results of the study show that reputation, religiosity, and transparency have a significant positive effect partially, as well as the results obtained simultaneously the three variables have a significant effect on the muzakki's trust in paying zakat at Baitul Mal Banda Aceh. Limitations - This study has limitations in terms of the relatively small number of samples and the internal measuring variable used in this study is only religiosity, it is better to add other variables that are internal Practical Implications - As a practical implication, the results of this research can be used as a reference by zakat organizations/institutions to maintain performance and continue to improve capacity and integrity, especially transparency in order to maintain the trust of existing muzakki and provide the sense of confidence to other prospective muzakki.